Hepatitis B Virus Reactivation in Gastrointestinal Stromal Tumor Patients Treated With Imatinib - Lei, Tianxiang; Tan, Fengbo; Hou, Zhouhua; Liu, Peng; Zhao, Xianhui; Liu, Heli (Frontiers in Oncology, 2021)
Purpose: Hepatitis B virus reactivation (HBVr) in patients with gastrointestinal stromal tumors (GISTs) have not been sufficiently characterized. This study aimed to review the possible mechanism of HBVr induced by imatinib and explore appropriate measures for patient management and monitoring. Methods: The clinical data of GIST patients who experienced HBVr due to treatment with imatinib at Xiangya Hospital (Changsha, Hunan, China) were retrospectively analyzed. A literature review was also conducted. Results: Five cased were analyzed, including 3 cases in this study. The average age of the patients was 61.8 y, with male preponderance (4 of 5 vs. 1 of 5). These patients received imatinib as adjuvant treatment (n=4) or as neoadjuvant treatment (n=1). Primary tumors were mostly located in the stomach (n=4) or rectum (n=1). High (n=3) or intermediate (n=1) recurrence risk was categorized using the postoperative pathological results (n=4). Imatinib was then started at 400 (n=4) or 200 mg (n=1) daily. Patients first reported abnormal liver function during the 2th (n=1),6th (n=3), or 10th (n=1) month of treatment with imatinib. Some patients (n=4) discontinued imatinib following HBVr; notably, 1 month after discontinuation, 1 patient experienced HBVr. Antivirals (entecavir n=4, tenofovir n=1), artificial extracorporeal liver support (n=1), and liver transplant (n=1) were effective approaches to treating HBVr. Most patients (n=3) showed favorable progress, 1 patient underwent treatment, and 1 patient died due to severe liver failure induced by HBVr. Conclusions: Although HBVr is a rare complication (6.12%), HBV screening should be conducted before starting treatment with imatinib in GIST patients. Prophylactic therapy for hepatitis B surface antigen positive patients, prompt antiviral treatment and cessation of imatinib are also necessary.